Residue degradation and metabolism of spinetoram in tea: A growing, processing and brewing risk assessment. (July 2021) - Li, Hongxia; Zhong, Qing; Luo, Fengjian; Wang, Xinru; Zhou, Li; Chen, Zongmao; Zhang, Xinzhong
Abstract: The degradation and metabolism of spinetoram in tea growth, processing and brewing were studied and analyzed by a modified QuEChERS coupled with UPLC-MS/MS method for the first time. The dissipation study showed that the half-life of spinetoram in fresh tea leaves was 0.70 d, and the metabolites N -formyl-XDE-175-J and N -demethyl-XDE-175-J were generated in tea growth. The degradation rates (DRs) of total spinetoram in green tea and black tea processing were 34.9%–57.8% and 36.9%–68.2%, and the transfer rates (TRs) were 5.1%–21.5% and 6.3%–27.7% from green tea and black tea into their infusion, respectively. Five days after spraying, the residue of spinetoram decreased more than 99% throughout the process from spraying to tea infusion, indicating that spinetoram has a lower residue amount in tea and tea infusion. The dietary risk assessment showed that the RQc and RQa were significantly less than 1, and the full dietary intake risk value was 8.78%. Thus, the MRL of spinetoram in tea can be set at 1 mg/kg with a pre-harvest interval (PHI) at 5 d to ensure safety for human consumption. Highlights: Spinetoram and its metabolites in different tea matrices were analyzed by a modified QuEChERS-UPLC-MS/MS method for the first time. Residue degradation and metabolism of spinetoram in tea growing, processing, and brewing chains were studied, with >99% of residues decreasing from tea gardens to cups. Spinetoram is suitable for usage in tea gardens, as it decreased rapidly in fresh tea leaves (t1/2 = 0.70 d) and due to its low total dietary intake risk (<8.78%).